Benefits of Using Decorrelated Color Information for Face Segmentation/Tracking. (3rd March 2008) - Ionita, Mircea C.; Corcoran, Peter
Abstract : We analyze in this paper the benefits that can be derived from employing color image alignment techniques in the context of face segmentation or tracking based on texture (defined as the patch of intensities) template matching. By making full use of the decorrelated color information, improvements on the accuracy of the segmentation are demonstrated. This is intended to enhance the face segmentation algorithm by increasing its robustness to differences in images caused by various image acquisition devices or settings or by variations in the ambient illumination conditions.